Penerapan Aplikasi Android “Menyusui Asi-Q” pada Ibu Menyusui di Wilayah Kerja Puskesmas Kota Palembang - Virgian, Kharisma; Setiawati, Desy; Veratiwi, Veratiwi; Franciska, Yunetra; Hakim, Dwi Ratnawaty (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2023)
The success of exclusive breastfeeding is determined by many factors, namely from the family, environment, health workers and the mother herself. Internal factors of the mother are the lack of knowledge about exclusive breastfeeding and the lack of awareness of the mother to provide exclusive breastfeeding. This community service activity is the result of research activities that have been carried out before. The results of the research were applied in the Implementation of the ASI-Q Breastfeeding Android Application for breastfeeding mothers in the work area of the Talang Ratu Palembang Health Center. This activity aims to apply the android application